2004
DOI: 10.1111/j.1365-2141.2004.05160.x
|View full text |Cite
|
Sign up to set email alerts
|

Different impacts of alleles αLEPRA and αLELY as assessed versus a novel, virtually null allele of the SPTA1 gene in trans

Abstract: Different impacts of alleles aLEPRA and a LELY as assessed versus a novel, virtually null allele of the SPTA1 gene in trans A subset of hereditary spherocytosis (HS) is associated with a reduction in red cell membrane spectrin (Agre et al, 1985). The SPTA1 gene, related to recessively inherited spherocytosis belongs to this subset. It is characterized by a pronounced and isolated decrease in spectrin. Under normal conditions, there is an overproduction of spectrin a-chains, however its extent has not been accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 18 publications
0
37
1
Order By: Relevance
“…A subset of patients presents with severe anemia in utero or immediately after birth and require red blood cell transfusion. 17-19 These patients frequently remain transfusion dependent and suffer from severe HS.…”
Section: Hereditary Spherocytosismentioning
confidence: 99%
“…A subset of patients presents with severe anemia in utero or immediately after birth and require red blood cell transfusion. 17-19 These patients frequently remain transfusion dependent and suffer from severe HS.…”
Section: Hereditary Spherocytosismentioning
confidence: 99%
“…Delaunay et al [34] identified compound heterozygous mutations in 2 alleles in a family in which the siblings had severe HS, αLEPRA (from the mother), and αLELY-Bicêtre (from the father; resulting in G→A at position 2377 in exon 51 of the lowly expressed polymor phic allele, αLELY, essentially a null mutation of a synthetic nonfunctional protein). The α-chain yield of αLEPRA and αLELY-Bicêtre is 16 and 0% of the normal amount, respectively.…”
Section: Molecular Genetic Mechanisms Of Five Hs-related Genesmentioning
confidence: 99%
“…SPTA1 aLELY (SPTA1 IVS45-12C>T), a common low-expression allele (Delaunay et al, 2004) was investigated. The proband harboured heterozygous aLELY inherited from his father, while it was absent from his mother and grandfather.…”
Section: Hereditary Elliptocytosis With Variable Expression and Incommentioning
confidence: 99%
“…These findings partially explained the variable expression between the proband and his mother. Delaunay et al (2004) reported that SPTA1 aLELY is adequately strong and may play no role in SPTA1-related HS. Herein, we found that SPTA1 aLELY may modify the phenotype of HE.…”
Section: Hereditary Elliptocytosis With Variable Expression and Incommentioning
confidence: 99%